The growth and aging of population - Mulligan, L. C. (Statistical and Social Inquiry Society of Ireland, 1959)
The population of the world was estimated at 1,094 million in 1850 and at 1,550 million in 1900 which represents an increase of 42 per cent, in that half-century. The population rose to 2,500 million in 1950, an increase of over 60 per cent in the first half of this century. For the remainder of the century expectations differ according to specific assumptions. Three assumptions have been made. On the improbable low assumption, the world population would reach 4,880 million by the year 2000; on the medium assumption, 6,270 and on the high assumption, 6,900. After studying the matter in all its aspects, the Population Branch of the United Nations has come to the conclusion that, barring either a catastrophe, or a deterioration of social conditions for progress in health of global proportions, a world population of between 6,000 and 7,000 million by the end of the century should now be expected almost as a matter of practical certainty.
Read before the Society, 20 October 1958
Keywords: World population; Population growth; World demographic trends; 314.15